Efficiency of physiotherapy with Caycedian Sophrology on children with asthma: A randomized controlled trial. Issue 5 (1st March 2018) - Romieu, Huguette; Charbonnier, Françoise; Janka, Dora; Douillard, Aymeric; Macioce, Valérie; Lavastre, Kathleen; Abassi, Hamouda; Renoux, Marie‐Catherine; Mura, Thibault; Amedro, Pascal
Abstract: Background: Asthma is the most common chronic disease in pediatrics. Along with the usual drug therapy using corticosteroids and bronchodilators, some interest has been shown for adjuvant therapies, such as sophrology. However, the level of evidence for non‐pharmaceutical therapies in asthma remains low, especially in children. This study aimed to assess whether in children with asthma, peak expiratory flow (PEF) improved more after a sophrology session alongside standard treatment than after standard treatment alone. Methods: We carried out a prospective randomized controlled clinical trial among 74 children aged 6‐17 years old, hospitalized for an asthma attack. Group 1: conventional treatment (oxygen, corticosteroids, bronchodilators, physiotherapy) added to one session of sophrology. Group 2: conventional treatment alone. The primary outcome was the PEF variation between the initial and final evaluations (PEF2 ‐PEF1 ). Results: Demographic and clinical characteristics were similar in both groups at baseline. Measures before and after the sophrology session showed that the PEF increased by mean 30 L/min in the sophrology group versus 20 L/min in the control group ( P  = 0.02). Oxygen saturation increased by 1% versus 0% ( P  = 0.02) and the dyspnea score with visual analogue scale improved by two points point ( P  = 0.01 ) . No differences were observed between the two groups in terms of duration of hospitalization, use and doses of conventional medical treatment (oxygen, corticosteroids, and bronchodilators), and quality of life scores. Conclusions: Sophrology appears as a promising adjuvant therapy to current guideline‐based treatment for asthma in children.